Developing a training course according to the strategic planning and thinking and measuring its effectiveness on the selection of university specialization by secondary school students in Dammam / Alqahtani Salam Alis - Alqahtani Salam , Alis (2019)
The objective of this study was to measure the effectiveness of a training unit according to planning and strategic thinking and its impact on the choice of specialization for secondary students in the scientific section in Dammam. The main objective of the study was to measure the effect of the training unit on the selection of the university specialization. The researcher used the semi-experimental approach for the equal groups through two experimental and control groups as it was the most appropriate approach to such studies. The research sample consisted of 95 students. The researcher used two tools: The training program, and achievement test. The researcher assumed four zero hypotheses in addition to the main question, where the most important results reached by the researcher as follow: There are statistically significant differences for the experimental group after training on the training module. In addition to that, results of the first hypothesis: There were statistically significant differences in favor of the experimental group in improving the scores of the achievement test in screening knowledge section for thinking preference measurement tools. Results of the second hypothesis: There are statistically significant differences in favor of the post-test result in the experimental group in screening knowledge section for Strategic thinking tool CORT. Also, Results of the third hypothesis show that there were statistically significant differences in favor of the post-test result in the experimental group in screening knowledge in strategic planning tools. In addition to that, the fourth result shows that there are statistically significant differences in favor of the post-test result in the experimental group in the circumstances that let the examined choose his major. This study recommends that the Ministry of Education adopts a gate similar to the talent gate called "Masar Gate" to be concerned with the meanings of planning and its tools and the programs of strategic thinking and its skills and a number of standards which clarify the meaning and tendency of personality by analyzing and linking with a number of university specializations or disciplines in the labor market or in voluntary work or in the field of entrepreneurship, this will be in accordance with the ambitious directions of the vision that the Kingdom seeks to achieve and employ these energies in the achievement of remarkable successes. There should be rehabilitation of students’ guides and counselors in the field of guidance of young people in the areas of thinking and strategic planning. Add a special course for planning and management in the curriculum and be a study or a chapter in some of the curriculum for the primary stage and then become an independent book with the extent and sequence of the school years. Focus on the concepts of planning and expressions through the wall paintings in schools and places frequented visited by school students. Build a number of non-grade programs for students, this program will take care of the planning concepts and be in the form of frequent meetings and graduated courses and training for students during the stages of study, especially secondary.